Effects of the MEK inhibitor, SL-327, on rewarding, motor- and cellular-activating effects of d-amphetamine and SKF-82958, and their augmentation by food restriction in rat - Carr, Kenneth D.; de Vaca, Soledad Cabeza; Sun, Yanjie; Chau, Lily S.; Pan, Yan; Dela Cruz, Julie (Psychopharmacologia, 2009)
Rationale Food restriction (FR) enhances learned and unlearned behavioral responses to drugs of abuse and increases D-1 dopamine (DA) receptor-mediated activation of extracellular signal-regulated kinases (ERK) 1/2 MAP kinase in nucleus accumbens (NAc). While a role has been established for ERK signaling in drug-mediated associative learning, it is not clear whether ERK regulates unconditioned behavioral effects of abused drugs. Objectives The purpose of this study was to determine whether blockade of ERK signaling, using the brain-penetrant MEK inhibitor, SL-327, decreases behavioral or NAc cellular responses to acute drug treatment and their augmentation by FR. Materials and methods Separate experiments assessed the effects of SL-327 (50 mg/kg, intraperitoneally) on (1) the reward-potentiating effect of d -amphetamine in an intracranial self-stimulation protocol, (2) the locomotor-activating effect of the D-1 agonist, SKF-82958, and (3) Fos-immunostaining induced in the NAc by SKF-82958. Results FR rats displayed enhanced responses to drug treatment on all measures. SL-327 had no effect on sensitivity to rewarding brain stimulation or the reward-potentiating effect of d -amphetamine. The MEK inhibitor, U0126, microinjected into the NAc was also without effect. The locomotor-activating effect of SKF-82958 was unaffected by SL-327. In contrast, SL-327 decreased NAc Fos-immunostaining and abolished the difference between feeding groups. Conclusions These results support the conclusion that ERK signaling does not mediate unlearned behavioral responses to drug treatment. However, the upregulation of ERK and downstream transcriptional responses to acute drug treatment may underlie the reported enhancement of reward-related learning in FR subjects.